Koesistensi Manusia dan Kera Ekor Panjang: Studi Multispecies di Kampung Pitu, Nglanggeran - Desy Wulandari (Jurnal Zona, 2024)
Conflicts between humans and wildlife especially in agricultural areas have yet to be resolved.Â  Wildlife is often regarded as pests, which leads to assessments of damage being made solely from the human perspective. This research conducted from January to February 2024 in Kampung Pitu, Nglanggeran Village, Gunungkidul District, directly observes interactions between humans and long-tailed macaques (Macaca Fascicularis). Utilizing a multispecies ethnographic approach, the study examines the everyday interactions between humans and long-tailed macaques. The findings indicate interactive adaptations between farmers and macaques. The research concludes that resolving conflicts between humans and wildlife requires a more holistic perspective, viewing long-tailed macaques not just as controllable entities. Adopting this perspective is expected to lead to fair multispecies policies